Electrophoretic separation techniques and their hyphenation to mass spectrometry in biological inorganic chemistry. Issue 7 (16th February 2016) - Holtkamp, Hannah; Grabmann, Gerlinde; Hartinger, Christian G.
Abstract : Electrophoretic methods have been widely applied in research on the roles of metal complexes in biological systems. In particular, CE, often hyphenated to a sensitive MS detector, has provided valuable information on the modes of action of metal‐based pharmaceuticals, and more recently new methods have been added to the electrophoretic toolbox. The range of applications continues to expand as a result of enhanced CE‐to‐MS interfacing, with sensitivity often at picomolar level, and evolved separation modes allowing for innovative sample analysis. This article is a followup to previous reviews about CE methods in metallodrug research ( Electrophoresis, 2003, 24, 2023–2037; Electrophoresis, 2007, 28, 3436–3446; Electrophoresis, 2012, 33, 622–634), also providing a comprehensive overview of metal species studied by electrophoretic methods hyphenated to MS. It highlights the latest CE developments, takes a sneak peek into gel electrophoresis, traces biomolecule labeling, and focuses on the importance of early‐stage drug development.